An Investigation Report on Durability Properties of Self Compacting Concrete Made with Recycled Fine Aggregates (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Self-compacting concrete (SCC) is a unique type of concrete that possesses the remarkable ability to be effortlessly placed within formwork without requiring external compaction through vibration. Introduced in Japan in 1988, SCC has rapidly gained widespread recognition and acceptance in Japan, Europe, and the USA, primarily due to its numerous inherent advantages. The utilization of SCC yields enhanced concrete quality, particularly in structural elements with complex reinforcement arrangements or areas where reducing permeability and improving concrete durability are crucial. SCC's most notable feature is its ability to flow freely and effortlessly into intricate formwork, thanks to its exceptional workability. This self-leveling property is achieved by incorporating specifically designed chemical admixtures that improve fluidity and cohesiveness without compromising the concrete's stability. Unlike conventional concrete, SCC eliminates the need for compaction through mechanical vibration, significantly reducing labor and time requirements during construction. The application of SCC is particularly advantageous in scenarios where reinforcing bars are densely packed or congested within the concrete element. Conventional concrete often struggles to fill such areas effectively, resulting in voids or inadequate compaction, compromising the structural integrity. In contrast, SCC's exceptional flowability ensures complete filling, resulting in a uniform and robust concrete matrix, effectively enhancing the overall quality and strength of the structure. Furthermore, SCC exhibits improved durability characteristics, contributing to its widespread adoption. The reduction in permeability achieved by SCC results in decreased water and chemical ingress, minimizing the likelihood of deterioration caused by corrosion or other chemical reactions. This enhanced durability extends the service life of structures, reducing the need for costly repairs and maintenance.